2016
DOI: 10.1002/smll.201600721
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity Polymer Visible‐Near Infrared Photodetectors via an Inverted Device Structure and Manipulation of Injection Barrier Height

Abstract: Visible-near infrared photodetectors are reported with excellent overall device parameters from conjugated polymers with different optical bandgaps by optimal design in device structure and optimizing the thickness of the photoactive layer in nanoscale. The best visible-near infrared photodetectors show high detectivity (D*) of 1.7 × 10(13) Jones at a wavelength of 710 nm, which is among one of the best results of polymer photodetectors reported to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 29 publications
5
47
0
Order By: Relevance
“…Several different low bandgap polymer/electron acceptor systems have been tested in organic photodetectors. [ 54–56 ] Also non‐fullerene acceptors have already proven to be useful in organic photodetectors. Y. Cao and coworkers reported a detectivity of 2 × 10 13 cm Hz 1/2 W −1 for a detector made of a polymer from the PTB‐family and NFA.…”
Section: Applicationsmentioning
confidence: 99%
“…Several different low bandgap polymer/electron acceptor systems have been tested in organic photodetectors. [ 54–56 ] Also non‐fullerene acceptors have already proven to be useful in organic photodetectors. Y. Cao and coworkers reported a detectivity of 2 × 10 13 cm Hz 1/2 W −1 for a detector made of a polymer from the PTB‐family and NFA.…”
Section: Applicationsmentioning
confidence: 99%
“…The common configurations of photodiodes can be categorized as the conventional and inverted type, in which the presence of interface layers is considered to effectively reduce the dark current for obtaining high detectivity, accompanied by low noise equivalent power (NEP) and large linear dynamic range (LDR). For photodiodes based on photovoltaic effect, an absorbed photon can generate at best one electron‐hole pair, resulting in the EQE of <100% . The collection of photogenerated carriers is assisted by the built‐in potential in the junction, which results from different work functions between anode and cathode.…”
Section: Fundamentals Of Photodetectorsmentioning
confidence: 99%
“…For photodiodes based on photovoltaic effect, an absorbed photon can generate at best one electron-hole pair, resulting in the EQE of <100%. [119][120][121][122][123][124][125][126][127][128] The collection of photogenerated carriers is assisted by the builtin potential in the junction, which results from different work functions between anode and cathode. And thus the external reverse bias is often used to improve charge collection efficiency.…”
Section: Photodiodementioning
confidence: 99%
“…Recently much effort has been made in the development of polymer photodiodes with broad spectral response, mainly through the design and synthesis of new donor‐type polymers, acceptor, and interlayer materials and modification of device structures . In 2015, Zhang et al reported polymer photodiodes with low dark current using donor polymers with the 3,4‐ethylenedioxythiophene moiety as side chains .…”
Section: Introductionmentioning
confidence: 99%